(untitled) (Contemporary Mathematics, 2023)
The preservation of sensitive data and prevention of unauthorized access are critical objectives in cloud computing environments, necessitating the implementation of robust security measures. The present study delves into the amalgamation of the Hierarchical Role Based Access Control Model (HR-ACM), Composikey, a composite key encryption algorithm, and Interactive Tree Based zero knowledge protocol (ITZKP) to construct a robust security framework for cloud security. This study presents an investigation into the viability and efficacy of integrating HRACM, Composikey, and ITZKP as a means of augmenting security measures and reducing potential hazards in cloudbased systems. The execution times comparison of the Composikey, IBPRE, and KPRE models were compared for different filesizes (1 KB to 2 GB) to evaluate the performance of the HRACM method. As roles increase, RBAC a execution time increases significantly. The HRACM Method takes 0.001 to 0.002 seconds to implement across all role counts. The results show that the HRACM Method is more efficient and time-effective than the RBAC Method. The response time measured in microseconds for the existing ZKP and Libra systems for different file sizes, ranging from 1KB to 1 GB. The results reveal that the verifier time for the ITZKP system aligns closely with the existing systems, demonstrating its ability to perform efficient verification processes. These findings collectively demonstrate the potential of the integrated security framework in enhancing cloud security.